2013
DOI: 10.1007/s11695-013-0926-y
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex Allows Fast-Track Bariatric Surgery

Abstract: Sugammadex allowed a safer and faster recovery from profound rocuronium-induced NMB than neostigmine did in patients with MO. Sugammadex may play an important role in fast-track bariatric anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 34 publications
3
61
2
2
Order By: Relevance
“…It appears that patients who were in deep NMB did not have enough adverse reactions for the anaesthetist to administer additional doses of the aforementioned medications. As opposed to Carron et al (19), our study clearly shows a reduction of operative time (laparascopic and total). This can be attributed to the 6 patients with moderate NMB, with bad working conditions.…”
Section: Discussioncontrasting
confidence: 98%
“…It appears that patients who were in deep NMB did not have enough adverse reactions for the anaesthetist to administer additional doses of the aforementioned medications. As opposed to Carron et al (19), our study clearly shows a reduction of operative time (laparascopic and total). This can be attributed to the 6 patients with moderate NMB, with bad working conditions.…”
Section: Discussioncontrasting
confidence: 98%
“…It is generally recommended to administer sugammadex according to the body weight [31]. In contrast, Loupec et al [32] advocate that in morbidly obese patients, 4 mgkg -1 sugammadex using ideal body weight provides satisfactory reversal of deep rocuronium-induced NMB.…”
Section: Obese Patientsmentioning
confidence: 99%
“…Muscle relaxants have also been dosed using ideal body weight; hovewer, recent publications using sugammadex for muscle relaxant reversal show that even doses for total body weight can be used without prolonging the procedure. [27] Due to these controversies of intravenous dosing, some authors suggest that using inhalational anesthesia results in faster awakening. [28] If total intravenous anesthesia is to be chosen, continuous monitorization with BIS (bispectral index) and using TCI (target controlled infusion) might be an option.…”
Section: Intraoperative Management Of the Morbidly Obese Patientmentioning
confidence: 99%
“…[26] Several modalities have been used to prolong the safe duration of apnea. [27] Another study has revealed that single lung ventilation in the morbidly obese is also possible if surgical and anesthesia teams work together and provide oxygenation breaks as needed. [28] Since fat tissue increases much more than lean tissue, morbidly obese individuals are relatively hypovolemic and anesthesia induction with acute vasodilation may cause acute or serious hypotension.…”
Section: Intraoperative Management Of the Morbidly Obese Patientmentioning
confidence: 99%